The Prediction of Visual Acuity after Open Globe Injury in Children Using Pediatric Ocular Trauma Score (POTS) - Albaaza Nuady; Purjanto Tepo Utomo; Widyandana Widyandana (Majalah Oftalmologi Indonesia, 2016)
Background: Open globe injury is one of the major causes of non-congenital ocular morbidities in children. Ocular trauma contributes 7% of all traumas and 10-15% of all ocular diseases. This study aims to assess VA after OGI in children at Sardjito General Hospital (SGH) and YAP Eye Hospital (YAP) using POTS.Methods: Children with OGI â‰¤15 years old from emergency unit from 2014 to 2016 was evaluated in retrospective design. Age, sex, admission time, operation time, cause of trauma, initial VA, final VA, and concomitant ocular pathology were collected, then classified with POTS. We compared initial VA and final VA to predict VA after OGI in children at SGH and YAP.Results: Twenty two (88%) patients were male and three (12%) patients were female with mean age of 8.84 years old. Nineteen cases were OGI with zone 1 involvement (76%), 2 cases with zone 2 (8%), and 4 cases with zone 3 (16%). After POTS classification, OGI in group 1 was 8 (32.6%), group 2 was 12 (48%), and group 3 was 5 (20%). Mean rate of initial VA was HM, 1 month after OGI was 1/60, 3 months was 3/60, 6 months was 3/60, and 12 months was 4/60. Classification using POTS was statistically significant for initial VA (p=0.046), VA in 1 month (p=0.046), and 3 months (p=0.46).Conclusion: OGI in children causes poor prognosis for VA. Zone involvement, delayed operation time and vitreous hemorrhage correlate with poor visual prognosis in OGI. Classification of injury with POTS shows prediction of VA after OGI.Â Keywords: open globe injury in children, pediatric ocular trauma score.